Benefits of various dextrans after delayed therapy in necrotizing pancreatitis of the rat - Schmidt, Jan; Huch, Kristina; Mithöfer, Kai; Hotz, Hubert G.; Sinn, Peter; Buhr, Heinz J.; Warshaw, A. L.; Herfarth, Christian; Klar, Ernst (Intensive care medicine, 1996)
Ultrahigh-molecular dextran (500 000 DA) has been shown to prevent pancreatic necrosis when given 30 min after induction of pancreatitis. This study should clarify the following: (a) are dextrans still effective after prolongation of the therapy-free interval? (b) what is the impact of the molecular weight of the dextrans? and (c) is their effect influenced by the dextran concentration or by the addition of hypertonic saline?
Gesehen am 20.08.2025